Engineering Chlorella-based consortia for sustainable food wastewater treatment: nutrient recovery, pollutant degradation and advanced harvesting - Lin Zhao; Shujie Wei; Yifan Zhang; Luguang Tao; Yuwei Xu; Yiming Wang; Zhangli Hu; Jun Tang; Song Wang (Environmental Research, 2026)

Structural color meets photoprotection: Chiral nanocellulose photonic powders functionalized with lignin nanoparticles - Jiyu Yang; Haixin Wang; Kai Feng; Zeqi Tang; Yiran Yang; Yuwei Qiu; Yadong Xu; Sheng Chen; Yuyue Zhong (Chemical Engineering Journal, 2026)

Enhanced electron transfer via Fe-Mn synergy in self-nitrogen biochar for rapid and efficient Cr(VI) removal - Yuting Zhang; Li Zhang; Yuwei Tang; Yilong Li; Weibin Sun; Zihao Yang; Jinchunzi Li; Shuang Liang; Jing Zhou (Biomass and Bioenergy, 2026)

Unraveling the different roles of enone oxidoreductases (FaEOs) in strawberry to improve aroma quality during cold storage - Pengpeng Sun; Quanzhi Wang; Yuan Ni; Zhiming Yan; Gang Li; Yuanhua Wang; Wei Chen; Qi Zhou; Pengcheng Zhao; Jialong Cheng; Bingxuan Li; Yuwei Tang; et al. (Postharvest Biology and Technology, 2026)

Artemisinin derivative SM934 targets α-enolase to inhibit PEP-mediated TAK1 stabilization and inflammation - Jun Pan; Yuwei Zhang; Zhiwei Du; Yuanyuan Huang; Yu Wang; Miya Su; Yuting Cai; Weiya Xu; Lili Chen; Chengdong Huang; Di Cui; Dongsheng Chen; et al. (Science China Life Sciences, 2026)

Elucidating Petal Coloration Differences in Eight Hibiscus rosa-sinensis Cultivars with Diverse Flower Colors using Multi-Dimensional Indicators - Xiaoyu Gao; Xianglu Jia; Dahong Su; Li Gong; Miaoqin Wei; Liqun Lei; Zhiqing Huang; Yuwei Tang; Zilong Ouyang; Weichao Teng (Journal of Plant Growth Regulation, 2026)

Substituting Chemical Fertilizer with Chicken Manure Alters Soil Dissolved Organic Matter and Volatile Organic Compound Profiles in Chinese Cabbage - Yuwei Zhang; Shan Tang; Qi Jin; Wei Gao; Ya-Li Li; Shao-Wen Huang; Hong Wang (Journal of Soil Science and Plant Nutrition, 2026)

PCSK9 orchestrates the antigen presentation–endothelial barrier axis to potentiate immune exclusion in colorectal cancer - Gang Wang; Zengyaran Yue; Yong Bian; Tingting Su; Hengyi Qi; Yuwei Zhang; Xu Wang; Weiwei He; Zhongqing Liang; Gang Yin; Decai Tang (Inflammation Research, 2026)

Identifying seasonal spatiotemporal differentiation and factor contributions to risk bundles of water ecosystem services in a river basin by machine learning - Jia Tang; Ling Liu; Yuwei Guo; Xijun Hu; Yuncai Wang (Journal of Cleaner Production, 2026)

Cyanidin-3-O-glucoside alleviates aflatoxin B1-induced splenic immunotoxicity via gut microbiota remodeling - Huiling Tang; Jordy Evan Sulaiman; Yuchen Zhang; Yuwei Yang; Jie Wang; Wujie Zhong; Hongtao Lei; Yunle Liu (Environmental Pollution, 2026)

Perfusion process-oriented metabolic engineering enhances 1,3-dihydroxyacetone production efficiency in Gluconobacter thailandicus - Yang Sun; Zilong Hu; Yuwei Shan; Rui Wang; Tang Liu; Kuiqi Jin; Qingxuan Miao; Cheng Ye; Jianqi Nie; Daiyin Zuo; Yinbiao Xu; Hua Li; et al. (Chemical Engineering Journal, 2026)

Human MAITregs possess diverse TCR repertoires and are functionally supported by glycolysis - Maoyu Tang; Xinying Li; Xudong Yang; Changfeng Zhao; Yuwei Zhang; Sanwei Chen; Zhenghui Ye; Liujin Hou; Yusheng Chen; Rong Lv; Hongchuan Zhao; Xiaowen Cheng; et al. (Science China Life Sciences, 2026)

Corrigendum to “Simultaneous nitrogen and phosphorus removal from low carbon-to-nitrogen ratio wastewater using an inorganic multi-electron donor autotrophic denitrification (MEDAD) biofilter: Feasibility, performance, and mechanisms” [J. Environ. Chem. Eng., 13:5 (2025) 119015] - Lin Zhao; Yifan Zhang; Yuwei Xu; Jun Tang (Journal of Environmental Chemical Engineering, 2026)

Applications of Piezoelectric Stimulation in Tissue Engineering - Beini Sheng; Jingrui Xing; Biao Song; Yuwei Gao; Hongmei Tang; Miao Xiao (Journal of Medical and Biological Engineering, 2026)

New insights into the characteristic flavor formation of Sichuan fermented sausages driven by liquid smoke addition: An integrated study based on microbiomics, flavoromics, and untargeted metabolomics - Dong Zhang; Xinrui Xie; Changlian Yu; Yuwei Liu; Li Yang; Chang Su; Xingzhong Zhang; Hongjun Li; Jie Tang (International Journal of Food Microbiology, 2026)

Investigation into auto-ignition characteristics and kinetics modeling of PODE2/n-heptane mixtures using an RCM - Xiaochen Wang; Jing Zou; Yingtao Wu; Jianbing Gao; Chenglong Tang; Ning Li; Yuwei Zhao (Fuel, 2026)

Effect of freezing and thawing on hydrothermal salts and deformation characteristics of unsaturated sulfate saline soils - Weidong Chang; Gang Li; Hua Tang; Yuwei Ma; Zhengyi Wang (Hydrogeology Journal, 2026)

Deciphering starch–protein interaction mechanisms in rice noodles: A synergistic perspective of starch chain architecture and starch granule size - Yiming Wang; Ning Tang; Dong-Hui Geng; Kuaitian Wang; Yuwei Li; Ebenezer Asiamah; Yongqiang Cheng (Food Research International, 2026)

Harnessing the application of functional polysaccharides in food packaging - Yuwei Wang; Hailong Bai; Shunjiang Jia; Qiao Zhang; Peng Zhao; Yuping Tang; Lizeng Peng; Elaine Lai-Han Leung (Trends in Food Science & Technology, 2025)

Promoting electron transfer and increasing oxygen vacancies on Cu-doped Co3O4 for enhanced peroxomonosulfate activation for tetracycline removal - Yin Zhu; Qian Tang; Kai Wu; Zhikai Zhang; Yuwei Sun; Wei Jiang; Yonghui Gao (Journal of Environmental Chemical Engineering, 2025)

Nanoengineering construction of Fe2O3/g-C3N4 heterojunctions for cooperative enhanced photocatalytic CO2 reduction and pollutant degradation - Yonggong Tang; Ziran Zhang; Fan Wu; Tao Xu; Yelei Li; Xin Zhou; Yuwei Pan; Guangyu Wu (Environmental Research, 2025)

Carboxymethyl chitosan-based form-stable phase change materials with ultra-low leakage and excellent low-temperature buffering performance - Dengshuang Guo; Yuwei Zhang; Kuncong Chen; Shun Wang; Zhongfeng Tang; Baofeng Lin (Carbohydrate Polymers, 2025)

Field experimental study of hydrothermal salt forces in rectangular canals in seasonally frozen soil region - Weidong Chang; Gang Li; Zhengyi Wang; Hua Tang; Yuwei Ma; Haoyuan Jiang (Journal of Hydrology, 2025)

Simultaneous nitrogen and phosphorus removal from low carbon-to-nitrogen ratio wastewater using an inorganic multi-electron donor autotrophic denitrification (MEDAD) biofilter: Feasibility, performance, and mechanisms - Lin Zhao; Yifan Zhang; Yuwei Xu; Jun Tang (Journal of Environmental Chemical Engineering, 2025)

Insight into the role of linear chains with and without branches in the structure and digestibility of rice starch gel during short-term and long-term retrogradation - Dong-Hui Geng; Ning Tang; Yuwei Li; Siyi Chen; Xiaojia Bian; Yiming Wang; Yongqiang Cheng (Food Hydrocolloids, 2025)

Dual-opto-CRISPRi-mediated dynamic regulation of fructose metabolism for high-efficiency D-allulose biosynthesis in E. coli - Yuwei Wang; Yingmengyu Qin; Tongjian Li; Dandan Tang; Yuting Lu; Wei Liu; Ling Jiang (Food Bioscience, 2025)

Dimensionality control of chiral covalent organic frameworks for enhanced asymmetric catalysis - Kai Zhang; Yuexin Zheng; Hong Chen; Dexuan Cai; Xihao Tang; Shengrun Zheng; Mubiao Xie; Jun Fan; Yuwei Zhang; Weiguang Zhang; Xinle Li; Songliang Cai (Chemical Engineering Journal, 2025)

Unveiling fungal degradation pathways for polyurethane and polyethylene through enrichment cultures and metabolic analysis - Eyalira Jacob Okal; Jie Zhou; Yanfei Wu; Tingfang Zhong; Yue Tang; Zhengyu Sun; Ruifang Xu; Yuwei Hu; Na Hu; Jingxian Li; Samantha C. Karunarathna; Peter E. Mortimer; et al. (International Biodeterioration & Biodegradation, 2025)

Cuphophyllus lijiangensis sp. nov. ( Hygrophoraceae , Agaricales ) from Yunnan, China - Lei Ye; Peter E. Mortimer; Song‐Ming Tang; Qianqian Tao; Guiqing He; Wengao Yang; Yuwei Hu (New Zealand Journal of Botany, 2025)
A new species of Cuphophyllus ( Hygrophoraceae , Agaricales ) was discovered in mixed coniferous and broad‐leaved forests (Pinaceae and Fagaceae) and grassland margins in Lijiang, North‐west Yunnan, and South‐west China. The species is described using morphological and molecular methods. Based on on‐site habitat observation data and a literature review, the novel species is best described as a saprobic macrofungus that thrives in soil humus within mixed pine forests or grasslands. The basidiomata of the novel species exhibit macroscopic similarities to C. virgineus ; however, C. lijiangensis sp. nov. differs primarily in having a smaller pileus, shorter stipe, larger basidiospores, and an intricate trichoderm pileipellis. Phylogenetic analysis, based on the combined rDNA internal transcribed spacer (ITS), nuc28S rDNA (28S), and RNA polymerase II subunit 2 ( rpb 2) genes, places C. lijiangensis in a clade with C. virgineus , C. borealis , C. yacurensis , and C . russocoriaceus . Both morphological characteristics and phylogenetic data support C. lijiangensis as a distinct new species within Cuphophyllus . This study provides a comprehensive description of the new species, colour photographs of basidiomata, micromorphological structures, and a phylogenetic tree to show the position of the new species.

Exploring the regulation of metabolic changes mediated by different combined starter cultures on the characteristic flavor compounds and quality of Sichuan-style fermented sausages - Buzhou Xu; Wenliang Qiu; Yuwei Liu; Fanyi Gong; Qian Liu; Jiaxin Chen; Yong Tang; Chang Su; Jie Tang; Dong Zhang; Hongjun Li (Food Research International, 2025)

Sodium bisulfite boosted exopolysaccharide production by Auxenochlorella protothecoides: Potential mechanisms harnessing H2O2 signaling and carbon reallocation - Rong Zhou; Wenli Zuo; Yuwei Xie; Yuting Wang; Chao Li; Yufang Tang; Zhenyao Wang; Yuqin Li (Bioresource Technology, 2025)

In vitro simulated digestive properties of Monascus vinegar melanoidins, and cytoprotective functions on Caco-2 cells - Kuaitian Wang; Yuwei Li; Xiaojia Bian; Chen Wang; Donghui Geng; Linwei Yu; Yongqiang Cheng; Hongbin Chen; Ning Tang (Food Research International, 2025)

SaTDT enhanced plant tolerance to NaCl stress by modulating the levels of malic acid and citric acid in cells - Xiangyu Wei; Li Xu; Suisui Dong; Nina He; Qianqian Xi; Dan Yao; Qianqian Wang; Yue Zuo; Chen Ling; Meiting Qi; Wen Bai; Kai Han; et al. (Plant Molecular Biology, 2025)

Low-potential bionic electrochemiluminescence sensing platform based on SnS2/CuNWs synergistic promotion for highly selective detection of glycocholic acid - Yuwei Wang; Shanshan Tang; Miao Liu; Wei Wang; Axin Liang; Aiqin Luo (Analytica Chimica Acta, 2025)

Human embryonic stem cell spheroids derived exosomal hsa_circ_0003258 sequestered dual targeting of miR-502-5p on KLF4/NF-κB and GALNT4/P53 to mitigate inflammation and apoptosis in hepatic ischemia reperfusion injury - Ning Wang; Yuwei Zhang; Shuai Zhang; Chuxin Chen; Haibin Wu; Peilin Liao; Shoupei Liu; Sen Chen; Xueyan Zhang; Jinghe Xie; Tingting Guo; Yan Liang; et al. (Chemical Engineering Journal, 2024)

Urea-modified hazelnut shell biochar (N-HSB) for efficient Cr(VI) removal: Performance and mechanism insights - Yuting Zhang; Yuwei Tang; Baoming Jin; Ruiping Yan; Li Zhang; Yilong Li; Jinchunzi Li; Shuang Liang (Journal of Contaminant Hydrology, 2024)

Simulation of the physiological and photosynthetic characteristics of C3 and C4 plants under elevated temperature and CO2 concentration - Wei Tian; Chenfei Su; Nan Zhang; Yuwei Zhao; Long Tang (Ecological Modelling, 2024)

Ferrocenedicarboxylate modified Bi-MOF for water decontamination via different advanced oxidation processes: Multifunction, mechanisms and biotoxicity test - Ya Gao; Fei Wang; Jie Tang; Chong-Chen Wang; Xiao-Hong Yi; Yuwei Wei; Guangchi Liu; Peng Wang; Huifen Fu; Chen Zhao; Xuchun Qiu; Shouliang Yi (Chemical Engineering Journal, 2024)

Integrated transcriptomic and metabolomic analyses revealed the effect of melatonin on delaying persimmon fruit softening - Yuwei Wang; Shiyu Lin; Mengyuan Zhang; Jiaojiao Nie; Aijun Tang; Ningjing Sun; Shuyu Zeng; Xiaofen Liu; Yuduan Ding; Xueren Yin; Qinggang Zhu (Postharvest Biology and Technology, 2024)

Simulation Study of Acid Fracturing Initiation with Consideration of Rock Mechanics Parameter Variations - Yuwei Li; Xingwen Jiang; Jizhou Tang; Bo Liu (Rock Mechanics and Rock Engineering, 2024)

Non-equilibrium compression achieving high sensitivity and linearity for iontronic pressure sensors - Jing Yang; Zhibin Li; Ying Wu; Yong Shen; Ming Zhang; Bin Chen; Guojiang Yuan; Songhua Xiao; Jiansong Feng; Xu Zhang; Yuwei Tang; Sunan Ding; et al. (Science Bulletin, 2024)

Geochemical characteristics, source analysis, influencing factors, and reserves of soil Selenium in Wuming, Guangxi, China - Jie Li; Xinyu Wang; Lei Wang; Yuwei Hu; Zhenhua Tang (Environmental Geochemistry and Health, 2024)

Boosting peroxymonosulfate activation with a composite of highly dispersed FeS2 nanoparticles anchored on N-doped biochar for efficient tetracycline degradation - Wenqi Bao; Qian Tang; Yixin Fan; Yin Zhu; Yonghui Gao; Yuwei Sun; Hao Liu (Journal of Environmental Chemical Engineering, 2024)

New butanolide derivatives from the marine derived fungus Aspergillus terreus GZU-31-1 by chemical epigenetic manipulation - Yuwei Zhou; Xiaocong Chen; Yuqian Tang; Yena Liu; Zhongxiang Zhao; Hui Cui (Natural Product Research, 2024)

A vertical-flow constructed wetland–microalgal membrane photobioreactor integrated system for treating high-pollution-load marine aquaculture wastewater: A lab-scale study - Lin Zhao; Jun Tang; Yuwei Xu; Yifan Zhang; Zihao Song; Guiping Fu; Zhangli Hu (Science of The Total Environment, 2024)

Satellite video single object tracking: A systematic review and an oriented object tracking benchmark - Yuzeng Chen; Yuqi Tang; Yi Xiao; Qiangqiang Yuan; Yuwei Zhang; Fengqing Liu; Jiang He; Liangpei Zhang (ISPRS Journal of Photogrammetry and Remote Sensing, 2024)

Day-ahead optimal scheduling of hydropower-dominated power grids under a spot market environment - Wenlin Yuan; Yingyi Sun; Chengguo Su; Yang Wu; Hangtian Guo; Yuwei Tang (Journal of Cleaner Production, 2024)

Rosa yangii (Rosaceae), a new species from China - Peifeng Lyu; Le Luo; Yuwei Tang; Xiaoling Tian; Chao Yu; Lijun Zhou; Lingna Zheng; Qixiang Zhang (Kew Bulletin, 2023)

Exploring the Therapeutic Effects and Mechanisms of Transcranial Alternating Current Stimulation on Improving Walking Ability in Stroke Patients via Modulating Cerebellar Gamma Frequency Band—a Narrative Review - Tingyi Feng; Lichao Zhang; Yuwei Wu; Lin Tang; Xixi Chen; Yuanli Li; Chunlei Shan (The Cerebellum, 2023)
The cerebellum plays an important role in maintaining balance, posture control, muscle tone, and lower limb coordination in healthy individuals and stroke patients. At the same time, the relationship between cerebellum and motor learning has been widely concerned in recent years. Due to the relatively intact structure preservation and high plasticity after supratentorial stroke, non-invasive neuromodulation targeting the cerebellum is increasingly used to treat abnormal gait in stroke patients. The gamma frequency of transcranial alternating current stimulation (tACS) is commonly used to improve motor learning. It is an essential endogenous EEG oscillation in the gamma range during the swing phase, and rhythmic movement changes in the gait cycle. However, the effect of cerebellar tACS in the gamma frequency band on balance and walking after stroke remains unknown and requires further investigation.

Heavy metals transport patterns and risk evaluation in the pig manure- black soldier fly-tilapia food chain - Changquan Lin; Xiting Xia; Yuwei Li; Rong Ma; Langping Zhu; Xiaotian Li; Youqian Tang; Chunming Wang (Environmental Pollution, 2023)

Carboxymethyl chitosan/sodium alginate hydrogel films with good biocompatibility and reproducibility by in situ ultra-fast crosslinking for efficient preservation of strawberry - Yuwei Zhang; Wenxin Zhao; Zhenhao Lin; Zhongfeng Tang; Baofeng Lin (Carbohydrate Polymers, 2023)

Removal performance and mechanisms of aqueous Cr (VI) by biochar derived from waste hazelnut shell - Yuting Zhang; Yuwei Tang; Ruiping Yan; Jinchunzi Li; Chenyang Li; Shuang Liang (Environmental Science and Pollution Research, 2023)

Investigation of the redox behavior of biochar-based bipolar electrochemistry in porous media - Hongwei Zhang; Haiyin Xu; Hui Zi; Yuwei Tang; Xijie Zheng; Ping Wang; Jing Huang; Honghui Wu; Peipei Song; linxin Wu; Zechen Liu; Wenshao Mao; et al. (Chemical Engineering Journal, 2023)

Hot-topics cross-propagation and opinion-transfer dynamics in the Chinese Sina-microblog social media: A modeling study - Fulian Yin; Yuwei She; Yanyan Pan; Xinyi Tang; Haotong Hou; Jianhong Wu (Journal of Theoretical Biology, 2023)

Dual-response fluorescent probe based on nitrogen-doped carbon dots and europium ions hybrid for ratiometric and on-site visual determination of oxytetracycline and tetracycline - Huifang Wu; Yubing Chen; Mengqi Xu; Yuwei Ling; Shiying Ju; Yanfeng Tang; Changlun Tong (Science of The Total Environment, 2023)

Four-armed host-defense peptidomimetics-augmented vanadium carbide MXene-based microneedle array for efficient photo-excited bacteria-killing - Xiaoqian Feng; Dongyi Xian; Jintao Fu; Rui Luo; Wenhao Wang; Yuwei Zheng; Qing He; Zhan Ouyang; Shaobin Fang; Wancong Zhang; Daojun Liu; Shijie Tang; et al. (Chemical Engineering Journal, 2023)

N-doped graphene aerogel cathode with internal aeration for enhanced degradation of p-nitrophenol by electro-Fenton process - Qian Tang; Sijia Luo; Hang Gao; Yixin Fan; Wenqi Bao; Yonghui Gao; Yuwei Sun; Chunwei Yang (Environmental Science and Pollution Research, 2022)

Spatio-temporal Distribution Characteristics and Environmental Impact Factors of Lung Cancer Mortality: A Case Study of Yuhui District in Bengbu City, China - Jingjing Tang; Kangkang Gu; Jing Mi; Wenhao Zhang; Yunhao Fang; Yuwei Li; Beichen Wang (Chinese Geographical Science, 2022)

Investigation on the characteristics of gut microbiota in critically endangered blue-crowned laughingthrush (Garrulax courtoisi) - Cong Wang; Jiawei Li; Yuwei Cheng; Hongbo Tang; Yanpeng Xiong; Yongfei Wu; Luping Wang; Daoqiang Liu; Jianhua Huang (Molecular Genetics and Genomics, 2022)

Remodeling of Arctic char ( Salvelinus alpinus ) lipidome under a stimulated scenario of Arctic warming - Chao Wang; Yufeng Gong; Fuchang Deng; Enmin Ding; Jie Tang; Garry Codling; Jonathan K. Challis; Derek Green; Jing Wang; Qiliang Chen; Yuwei Xie; Shu Su; et al. (Global Change Biology, 2021)
Arctic warming associated with global climate change poses a significant threat to populations of wildlife in the Arctic. Since lipids play a vital role in adaptation of organisms to variations in temperature, high‐resolution mass‐spectrometry‐based lipidomics can provide insights into adaptive responses of organisms to a warmer environment in the Arctic and help to illustrate potential novel roles of lipids in the process of thermal adaption. In this study, we studied an ecologically and economically important species—Arctic char ( Salvelinus alpinus )—with a detailed multi‐tissue analysis of the lipidome in response to chronic shifts in temperature using a validated lipidomics workflow. In addition, dynamic alterations in the hepatic lipidome during the time course of shifts in temperature were also characterized. Our results showed that early life stages of Arctic char were more susceptible to variations in temperature. One‐year‐old Arctic char responded to chronic increases in temperature with coordinated regulation of lipids, including headgroup‐specific remodeling of acyl chains in glycerophospholipids (GP) and extensive alterations in composition of lipids in membranes, such as less lyso‐GPs, and more ether‐GPs and sphingomyelin. Glycerolipids (e.g., triacylglycerol, TG) also participated in adaptive responses of the lipidome of Arctic char. Eight‐week‐old Arctic char exhibited rapid adaptive alterations of the hepatic lipidome to stepwise decreases in temperature while showing blunted responses to gradual increases in temperature, implying an inability to adapt rapidly to warmer environments. Three common phosphatidylethanolamines (PEs) (PE 36:6|PE 16:1_20:5, PE 38:7|PE 16:1_22:6, and PE 40:7|PE 18:1_22:6) were finally identified as candidate lipid biomarkers for temperature shifts via machine learning approach. Overall, this work provides additional information to a better understanding of underlying regulatory mechanisms of the lipidome of Arctic organisms in the face of near‐future warming.

LhGST is an anthocyanin-related glutathione S-transferase gene in Asiatic hybrid lilies (Lilium spp.) - Yuwei Cao; Leifeng Xu; Hua Xu; Panpan Yang; Guoren He; Yuchao Tang; Xianyu Qi; Meng Song; Jun Ming (Plant Cell Reports, 2021)

Heterosis-associated genes confer high yield in super hybrid rice - Tianzi Lin; Cong Zhou; Gaoming Chen; Jun Yu; Wei Wu; Yuwei Ge; Xiaolan Liu; Jin Li; Xingzhou Jiang; Weijie Tang; Yunlu Tian; Zhigang Zhao; et al. (Theoretical and Applied Genetics, 2020)
Key message Heterosis QTLs, including qSS7 and qHD8, with dominance effects were identified through GBS and large-scale phenotyping of CSSLs and hybrid F 1 populations in a paddy field. Abstract Heterosis has contributed immensely to agricultural production, but its genetic basis is unclear. We evaluated dominance effects by creating two hybrid populations: a B-homo set with a homozygous background and heterozygous chromosomal segments and a B-heter set with a heterozygous background and homozygous segments. This was achieved by crossing a set of 156 backcrossed-derived chromosome segment substitution lines (CSSLs) with their recurrent parent (9311), the male parent of the first super-high-yield hybrid Liangyoupei9 (LYP9), and with the female parent (PA64s) of the hybrid. The CSSLs were subjected to a genotyping-by-sequencing analysis to develop a genetic map of segments introduced from the PA64s. We evaluated the heterotic effects on eight yield-related traits in the hybrid variety and F 1 populations in large-scale field experiments over 2 years. Using a linkage map consisting of high-density SNPs, we identified heterosis-associated genes in LYP9. Five candidate genes contributed to the high yield of LYP9, with qSS7 and qHD8 repeatedly detected in both B-hybrid populations. The heterozygous segments harboring qSS7 and qHD8 showed dominance effects that contributed to the heterosis of yield components in the hybrid rice variety Liangyoupei9.

Heme oxygenase 1 plays a crucial role in swamp eel response to oxidative stress induced by cadmium exposure or Aeromonas hydrophila infection - Yuwei Zang; Shuting Zheng; Fang Tang; Long Yang; Xiping Wei; Dan Kong; Wenxiu Sun; Wei Li (Fish Physiology and Biochemistry, 2020)

Mechanism of exogenous cytokinins inducing bulbil formation in Lilium lancifolium in vitro - Guoren He; Panpan Yang; Yuchao Tang; Yuwei Cao; Xianyu Qi; Leifeng Xu; Jun Ming (Plant Cell Reports, 2020)

AGONOTES: A Robot Annotator for Argonaute Proteins - Lixu Jiang; Min Yu; Yuwei Zhou; Zhongjie Tang; Ning Li; Juanjuan Kang; Bifang He; Jian Huang (Interdisciplinary Sciences: Computational Life Sciences, 2020)

Direct Z-scheme La1-xCexMnO3 catalyst for photothermal degradation of toluene - Yiran Tang; Yuwei Tao; Ting Zhou; Baozhu Yang; Qing Wang; Zerui Zhu; Aijuan Xie; Shiping Luo; Chao Yao; Xiazhang Li (Environmental Science and Pollution Research, 2019)

Modulation of Beta Oscillations for Implicit Motor Timing in Primate Sensorimotor Cortex during Movement Preparation - Hongji Sun; Xuan Ma; Liya Tang; Jiuqi Han; Yuwei Zhao; Xuejiao Xu; Lubin Wang; Peng Zhang; Luyao Chen; Jin Zhou; Changyong Wang (Neuroscience Bulletin, 2019)

Comparison of Greenhouse and Field Degradation Behaviour of Isoprocarb, Hexaflumuron and Difenoconazole in Perilla frutescens - Caixia Sun; Hu Zhang; Tao Tang; Mingrong Qian; Yuwei Yuan; Zhiheng Zhang (Bulletin of Environmental Contamination and Toxicology, 2012)

A proteomic investigation into adriamycin chemo-resistance of human leukemia K562 cells - Xingchen Peng; Fengming Gong; Gang Xie; Yuwei Zhao; Minghai Tang; Luoting Yu; Aiping Tong (Molecular and Cellular Biochemistry, 2011)